Maqasid al-shariah in Islamic banks: before and after Value-Based Intermediation (VBI) implementation / Fateha Abd Halim, Tengku Dewi Ahdiyaty Tengku Ahmad Mazlin - Abd Halim, Fateha; Tengku Ahmad Mazlin, Tengku Dewi Ahdiyaty (Arshad Ayub Graduate Business School, 2018)
Maqasid al-shariah or ‘the objectives of Shariah’ is known to preserve the five basic elements, namely religion, life, intellect, lineage and wealth. Last year, Bank Negara Malaysia (BNM) had published a strategy paper entitled “Value-based Intermediation (VBI): Strengthening the Roles and Impact of Islamic Finance” which touched on how the Islamic banking industry could act as a tool to achieve maqasid al-shariah. The introduction of VBI by BNM was due to the lack of awareness and implementation of maqasid al-shariah by various Islamic banks. Generally, achieving maqasid al-shariah should be the primary focus of most if not all Islamic banks, yet, was not implemented as observed by BNM. It had also signified a concern regarding the operations of Islamic banks which did not represent or promote the true concept of maqasid al-shariah within their institutions. Thus, this study aims to highlight the concept of maqasid al-shariah that should be realized in Islamic banks. In addition, this study also aims to identify the efforts of Islamic banks in realizing the maqasid al-shariah through their products and services before and after VBI implementation. The last objective of this study is to determine the challenges faced by Islamic banks in the realization of maqasid al-shariah through VBI. Moreover, a qualitative method was adopted as the main research methodology for this study whereby information on the practices of three Islamic banks in Malaysia including Bank Islam Malaysia Berhad (BIMB), Maybank Islamic Berhad and Bank Pertanian Malaysia Berhad (Agrobank) was gained from semi-structured interviews conducted with bankers directly involved with VBI implementation in the Shariah department or division in each bank. Researchers found that the concept of maqasid al-shariah that had to be realized in Islamic banks was to provide products and services which could protect religion, life, intellect, lineage and wealth. This study also discovered that maqasid al-shariah had been realised in Islamic bank operations in the provision of Islamic banking products and services before and after VBI implementation, whilst being more structured after VBI implementation. There are altogether four challenges faced by the Islamic banks in implementing VBI which are structural issue, high risk segment, lack of awareness and demand and market competitiveness. In tandem, other Islamic banks are encouraged to implement VBI as it could give positive impacts on the application of maqasid al-shariah for the bank as well as to aid in further study of the reasons why some Islamic banks are not implementing VBI. The finding of this research could benefit the industry by enlightening the impacts of VBI to the Islamic finance industry